2020
DOI: 10.1186/s13643-020-01376-9
|View full text |Cite
|
Sign up to set email alerts
|

Locating unregistered and unreported data for use in a social science systematic review and meta-analysis

Abstract: Meta-analysts rely on the availability of data from previously conducted studies. That is, they rely on primary study authors to register their outcome data, either in a study's text or on publicly available websites, and report the results of their work, either again in a study's text or on publicly accessible data repositories. If a primary study author does not register data collection and similarly does not report the data collection results, the meta-analyst is at risk of failing to include the collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Traditionally, the correlation between the interaction term and other variables is not reported and often must be requested directly from the original authors. Doing so is a high-risk endeavor given researchers' traditionally low response rate (Aguinis, Beaty, Boik, & Pierce, 2005;Polanin et al, 2020a), but the rise of Open Science and the concomitant Individual Participant Data (IPD) means that this information is increasingly available. Amalgamating IPD across multiple studies is usually referred to as a megaanalysis, and, as suggested here, can be used to supplement a standard meta-analysis (Boedhoe et al, 2019;Kaufmann, Reips, & Merki, 2016).…”
Section: Average Effect Sizesmentioning
confidence: 99%
“…Traditionally, the correlation between the interaction term and other variables is not reported and often must be requested directly from the original authors. Doing so is a high-risk endeavor given researchers' traditionally low response rate (Aguinis, Beaty, Boik, & Pierce, 2005;Polanin et al, 2020a), but the rise of Open Science and the concomitant Individual Participant Data (IPD) means that this information is increasingly available. Amalgamating IPD across multiple studies is usually referred to as a megaanalysis, and, as suggested here, can be used to supplement a standard meta-analysis (Boedhoe et al, 2019;Kaufmann, Reips, & Merki, 2016).…”
Section: Average Effect Sizesmentioning
confidence: 99%
“…If the authors implemented a general violence or bullying prevention program but did not include a cyberbullying measure, we did not immediately exclude it. This procedure and the reasoning behind it have been explained by Polanin et al (37). They found that excluding the identified studies would change some substantive conclusions in their metaanalysis.…”
Section: Data Collection 211 Inclusion/exclusion Criteriamentioning
confidence: 95%
“…One further limitation of this method is that it relies on cooperation from other researchers to locate, and sometimes re-analyse, unpublished data. These factors often mean that attempts to find unpublished studies returns a low yield (Polanin, Espelage, et al, 2020). Indeed, we (Saunders & Inzlicht, 2020) only uncovered 7 unpublished effect sizes-two of which were from our own laboratory.…”
Section: Emptying the File-drawer By Finding Unpublished Effect Sizesmentioning
confidence: 89%